1990
DOI: 10.1177/004051759006001205
|View full text |Cite
|
Sign up to set email alerts
|

SEM Studies of the Surface and Fracture Morphology of Pineapple Leaf Fibers

Abstract: The structural features and fracture morphology of raw and chemically treated pineapple leaf fiber have been studied using scanning electron microscopy. Pineapple leaf has a multicellular structure, and alkali treatment clearly reveals the ultimate fibers. Surface morphology progressively changes with gradual removal of noncehulosic constituents like lignin and hemicellulose. Fracture morphology shows that there is a uniform sharing of the load in the ultimate fibers of raw pineapple leaf, whereas treated leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…During fiber extraction, most of the surface waxes and other noncellulosic substances are removed, as shown in Figure 2. When agro-based fibers are used as reinforcing fibers for composites, the removal of surface waxes and encrusting substances makes the fiber surface rough and improves the adhesion of fibers and polymer matrix [27,28]. The presence of impurities on the surface of the fibers affects the appearance and processability of the fibers [10].…”
Section: Fiber Structurementioning
confidence: 99%
“…During fiber extraction, most of the surface waxes and other noncellulosic substances are removed, as shown in Figure 2. When agro-based fibers are used as reinforcing fibers for composites, the removal of surface waxes and encrusting substances makes the fiber surface rough and improves the adhesion of fibers and polymer matrix [27,28]. The presence of impurities on the surface of the fibers affects the appearance and processability of the fibers [10].…”
Section: Fiber Structurementioning
confidence: 99%
“…11,12 Till date, PALFs have been studied for their mechanical and structural properties and compatibility toward many polymer matrixes such as polycarbonate, vinyl ester, high-density polyethylene, low-density polyethylene, polypropylene, polybutylene, and succinate. 13 –38 Only few studies have been reported for kinetic analysis of natural fibers. 39 46…”
Section: Introductionmentioning
confidence: 99%
“…Natural fibers have little resistance towards environmental influences and show an intrinsic variability of their properties. Hence, the use of natural fibers depends on the environmental conditions which are likely to influence ageing and degradation effects [4].Agave Americana L. is a monocotyledon plant, which belongs to the amaryllidaceae family (Figure 1). This species of Agave originates from Central America and is abundantly available in several regions of North Africa.…”
mentioning
confidence: 99%